Analisis Visi, Misi, dan Tujuan Pendidikan terhadap Peraturan Menteri Pendidikan Nasional Nomor 19 Tahun 2007 - Rahmawati, Putri Rizqiyah; Rahmawati, Nushrotul Hasanah; Sugiyanto, Fadilah Nur (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2024)
This research wants to know about the relevance of the vision, mission and goals of education at MI Muhammadiyah PK Sindon 1 to Permendiknas no. 19 of 2007 as an indicator. Choosing this MI because there is implicitly a lack of synchrony between its Vision and Mission so it is interesting to research further. This research is descriptive in nature, namely research that interprets the relevance of the vision, mission and educational objectives of MI Muhammadiyah PK Sindon 1. The data obtained used qualitative research, data collection techniques were carried out through observation and interviews as well as literature study. The results of the analysis are basically as follows: there are several points in the Vision, Mission and Educational Goals that are not in accordance with the Indicators of Minister of National Education Regulation No. 19 of 2007, as well as the irrelevance of the Vision, Mission and Educational Goals themselves. With this research, it is hoped that there will be improvements to the Vision, Mission and Goals of Education in order to achieve the overall National Education goals.